Analisis Pola Evolusi pada Pengembangan Perangkat Lunak melalui Aktivitas Repository Github dalam Project Based Learning - Mutia Rahmi Dewi; Defni; Yoliza Erwanda (Journal of Electrical Vocational Education, 2025)
Software evolution is a continuous process of change that occurs throughout the system development life cycle. In the context of higher education, understanding the dynamics of software change is essential for assessing students’ competencies in managing team-based projects. This study aims to analyze software evolution patterns in student projects developed using the Project-Based Learning (PBL) approach. The research data were obtained from 12 public GitHub repositories belonging to students who developed applications based on the Laravel framework. The study employs a descriptive quantitative approach by analyzing commit log data using automated Python-based scripts. The analysis focuses on activity metrics such as the number of commits, the average number of files changed per commit, and the identification of the most frequently modified files. The results indicate that each group exhibits distinct construction and evolution patterns. Groups with high commit frequencies demonstrate stable iterative development processes, whereas groups with low commit frequencies tend to perform large, sporadic changes. Frequent small changes on average indicate the adoption of good continuous integration practices. These findings confirm that software evolution dynamics in PBL are influenced not only by project size but also by collaboration patterns and the maturity of version control system usage. The results of this study are expected to serve as a foundation for developing automated, data-driven evaluation systems based on students’ development activities, as well as to enrich empirical studies on software evolution in vocational education.